Novel vaccination strategies based on optimal stimulation of CD4+ T helper cells for the treatment of oral squamous cell carcinoma - Azzi, Lorenzo; Celesti, Fabrizio; Chiaravalli, Anna Maria; Shaik, Amruth Kaleem Basha; Shallak, Mariam; Gatta, Andrea; Battaglia, Paolo; La Rosa, Stefano; Tagliabue, Angelo; Accolla, Roberto Sergio; Forlani, Greta (Frontiers in Immunology, 2024)
Oral Squamous Cell Carcinoma (OSCC) is the most common malignant tumor of the oral cavity.Despite recent advances in the field of oral cancer therapy, including the introduction of immunotherapeutic approaches, the 5-year survival rate remains steadily assessed around 50%. Thus, there is an urgent need for new therapeutic strategies. After the characterization of the immune phenotype of three human OSCC cell lines (CAL-27, SCC-25, and SCC-4) and one mouse OSCC cell line (MOC2) showing their similarities to resected patient tumors, we explored for the first time an experimental preclinical model of therapeutic vaccination with mouse OSCC MOC2 cell line stably expressing MHC class II antigens after CIITA gene transfection (MOC2-CIITA). Mice injected with MOC2-CIITA reject or strongly retard tumor growth; more importantly, vaccinated animals that fully reject MOC2-CIITA tumors display anti-tumor immunological memory protective against challenge with parental MOC2 tumor cells. Further experiments of adoptive cell transfer or in vivo cell depletion show that both CD4 + and CD8 + T lymphocytes prove fundamental in tumor rejection.This unprecedented approach for oral cancer opens the way for possible future translation of novel immunotherapeutic strategies to the human setting for the treatment of this tumor.